A Study of The Relationship between Dean Leadership Behavior and Instructor Professionalism Perceived by Instructors in The University of Lagos, Nigeria - Oluwatobiloba, Ogungbade Omobolanle; Eamoraphan, Suwattana (Scholar: Human Sciences, 2016)
The purpose of this study was to determine if there is a significant relationship between Dean Leadership behavior and instructor professionalism. The objectives of this research study focuses on what is the level between Dean leadership behavior and instructor professionalism as well as the relationship between Dean leadership behavior and instructor professionalism all perceived by instructors at the faculty of education, university of Lagos Nigeria. The research study were conducted among 200 instructors from the faculty of education university of Lagos, Nigeria in the mid-west of Africa and questionnaire was used as an instrument to administered questions to instructors regarding their perceptions on the relationship between Dean leadership behavior and instructor professionalism. A Likert scale questionnaire was used which was based on performance pyramid 20 by George Manning and Kent Curtis (2012) and leadership behavior of House’s path goal theory to give validity and reliability to the study. The data collected were analyzed accordingly by using different statistical method such as frequency, percentage, mean and standard deviations and Pearson Product Moment Correlation Analysis. According to these research studies, the research findings shows that the level of Dean Leadership behavior and instructor professionalism perceived by instructor is high and also there is significant relationship between Dean Leadership behavior and instructor professionalism. The findings could be useful for the administrators to evaluate their relationship with their instructors as the study implies. It can also be useful for Instructors to have a good and horizontal relationship between their co – instructors and students. Instructors should also create professional learning environment for themselves as that will enable them to have a mutual understanding with their Dean leadership behavior and promote team work spirit among them, their Dean and help them to improve on their teaching skills thus, promoting instructor professionalism and finally this research can be useful for future research in the area of Dean leadership behavior and instructor professionalism